THE IMPORTANCE OF A BALANCED DIET IN DAILY LIFE: A COMPREHENSIVE LITERATURE REVIEW (ACUMEN: INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH, 2026)
A balanced diet constitutes the cornerstone of human health, influencing virtually every physiological system from cellular metabolism to cognitive function. This literature review synthesizes current evidence on the multifaceted impacts of dietary patterns on health outcomes, disease prevention, and quality of life. We examine the optimal distribution of macronutrients, the critical roles of micronutrients, and the emerging understanding of diet-microbiome interactions